Pengaruh kompensasi terhadap kinerja karyawan pada PT Penta Rekayasa Bandung - Pratiwi, Gusti Ratih; Arwiyah , Muhammad Yahya (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Human resource management is an important component of every organization. This is due to the fact that it is directly related to effectiveness, which will lead to an increase or decrease in the amount of money a company generates. This study aims to determine the effect of compensation on employee performance at PT. Penta Engineering Bandung. The research method used is descriptive-qualitative with a quantitative approach. The authors of this study surveyed 30 people as a first step in examining the relationship between pay and productivity. When comparing employee performance with positive results, the organization's remuneration strategy reflects employee dissatisfaction. The results of this research and the descriptive analysis of this study on the compensation variable yield an overall average percentage of 82.8%, placing it in the good category and indicating that the company provides satisfactory salaries to its employees. Descriptive analysis of employee performance characteristics shows an average percentage of 86.8%, placing this result in a very good range. At an impact level of 28.7%, compensation is very influential in determining performance